1-Thiazol-2-yl-N-3-methyl-1H-pyrozole-5-carboxylic acid derivatives as antitumor agents. Issue 18 (15th September 2017) - Cooper, Alan B.; Ciblat, Stephane; Shipps, Gerald; Levine, Jedd; Kostura, Matthew; Oza, Vibha; Constantineau-Forget, Lea; Dery, Martin; Grand-Maitre, Chantal; Bruneau-Latour, Nicolas; Bellavance, Edith; Siddiqui, Arshad; et al.
Graphical abstract: Abstract: A class of substituted 1-thiazol-2-yl-N-3-methyl-1H-pyrozole-5-carboxylic acid derivatives was found to have potent anti-proliferative activity against a broad range of tumor cell lines. A compound from this class (14 ) was profiled across a broad panel of hematologic and solid tumor cancer cell lines demonstrating cell cycle arrest at the G0/G1 interphase and has potent anti-proliferative activity against a distinct and select set of cancer cell types with no observed effects on normal human cells. An example is the selective inhibition of human B-cell lymphoma cell line (BJAB). Compound14 was orally bioavailable and tolerated well in mice. Synthesis and structure activity relationships (SAR) in this series of compounds are discussed.